Removing welfare traps: Employment responses in the Finnish basic income experiment - Jouko Verho; Kari Hämäläinen; Ohto Kanninen (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
This paper provides evidence that replacing minimum unemployment benefts with a basic income of equal size has minor employment effects at best. We examine an experiment in Finland in which 2,000 beneft recipients were randomized to receive a monthly basic income. The experiment lowered participation tax rates by 23pp for full-time employment. Despite the considerable increase in work incentives, days in employment remained statistically unchanged in the frst year of the experiment. Moreover, even though all job search requirements were waived, participation in reemployment services remained high.
Keywords: C93; H55; I38; J65; 330; Employment; Field experiment; Social insurance; Unemployment benefits